The Development of Local Food Wisdom for the Elderly of Wiang Nuea Sub-district, Wiang Chai District, Chiang Rai Province - Sepha, Wasana; Manowang, Jiraporn; Phaphothirat, Kritsanakan (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
The purpose of this research was to study wisdom and develop traditional recipes for the elderly of Wiang Nuea Sub-district, Wiang Chai District, Chiang Rai Province. It was a qualitative and operational research. Purposive sampling was used to collect data from a informant group of 20 people, including the elderly, those with knowledge and wisdom in local food, wisdom teachers who participate in the process of generating food recipes, and community leaders. In-depth interviews, participatory behavior observation forms, forums, and the production of local cuisine recipes using qualitative data and content analysis were used as research methodologies. The study's findings revealed that 1) local food wisdom was inherited from grandparents and culturally passed down from generation to generation until now. People in the community enjoyed eating jackfruit curry to promote their Buddhist beliefs through customs such as the Songkran Festival or the New Year of the City. Furthermore, the belief of Kang Kha Nun is that it is an auspicious curry to make their lives prosperous, and Kaeng Khae should be eaten during the changing seasons since Kaeng Khae is a meal that employs a lot of herbs and vegetables and can prevent fever. Local foods commonly consumed in the community include Nam Prik Pla, Kaeng Phak Ho Pla Haeng, Kaeng Bon Kaep Moo, Kaeng Kae Jin Haeng, Larb Moo, Jor Phak Kad, Crab Chili Paste, Olive Chili Paste, Ta Dang Chili Paste, Aep Pla, Khao Tom Hua Ngork, Khanom Jok, and herbal juices such as lemongrass juice, pandan leaf juice, and butterfly pea juice. 2) In the development of local recipes of the elderly in Wiang Nuea Sub-district, Wiang Chai District, Chiang Rai, the researcher and the elderly in the community jointly analyzed the development guidelines by developing recipes according to wisdom to get the appropriate appearance and taste while still maintaining the traditional identity of wisdom by experimenting and developing in terms of appearance, taste, meticulousness, and color of food for three times to get four standard recipes, namely Aep Pla, Kaeng Phak Ho, Kaeng Bon, Nam Prik Pla, and herbal drinks.